Jaringan Komunikasi dalam Penanganan Gizi Balita di Posyandu Desa Medalem Kecamatan Tulangan Kabupaten Sidoarjo - Ainur Rochmaniah; Muhammad Syamsudin (Kanal: Jurnal Ilmu Komunikasi, 2018)
Child nutrition problems is an important thing that concerns parents in maintaining growth of children. Based on observation in Medalem on june 2016 have beenfound 4 cases, is 2 obesity cases of child and 2 malnutrition cases of child. This is indicates an increase incasesof child nutrition problems from 2014. There are socialization activities of infant and child feeding and child nutrition handling by midwives and Posyandu cadres. The purpose of this study is analyze and describe the pattern of information flow about child nutrition in Medalem. The type of this study is quantitative research using communication network analysis techniques. The sample of this study is using snowball sampling techniques. The result of this study are;(1) the patter of communication network formed is Wheel network (formal), gossip network (informal) and all channels network; (2)The opinion leaders in communication network has an important role to influenceing the people who are in the area of communication nerwork;(3) Based on the pattern of communication network, the opinion leaders have high heterogeneity in the level of mastery of innovation abaout nutrition of the toddler and choose a multi direction communication relationship in the communication process so that opinion leaders included in innovative society.